PENGARUH UKURAN PERUSAHAAN DAN OPINI AUDIT TERHADAP KETEPATAN WAKTU PUBLIKSAI PELAPORAN KEUANGAN (Studi Pada Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar Di Indeks Saham Syariah Indonesia ISSI Periode 2019-2021) - Erik Mandala Putra; Usdeldi; Achyat Budianto (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to find out whether the variable company size and audit opinion have an effect on the timeliness of publication of financial reports for food and beverage manufacturing companies listed on the Indonesian Sharia Stock Exchange (ISSI) and also listed on the Indonesia Stock Exchange for the 2019-2021 period. The population in this study are all manufacturing companies in the food and beverage sub-sector which are listed on the Indonesian Sharia Stock Exchange (ISSI) and also listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sampling technique used purposive sampling. 16 manufacturing companies in the food and beverage sub-sector were obtained which were listed on Indonesian Sharia Stocks for the 2019-2021 period as research samples. This research is a quantitative study using secondary data in the form of the company's annual financial reports. The analytical method used in this study is binary logistic regression assisted by the IBM SPSS statistics 25.0 application. The results of this study indicate that the firm size variable has no effect on the timeliness of financial reporting publication, while the audit opinion variable has a significant effect on the timeliness of financial reporting publication. Simultaneously the independent variables, namely company size and audit opinion, have an effect on the timeliness of financial reporting publication.